Publications on aspects of veterinary public health - Blackmore, DK (Massey University, 1989)
This application, to be examined for the degree of Doctor of Science (Massey University), is based on work which could be broadly classified under the heading of veterinary public health. The 1956 W.H.O. definition of veterinary public health is "the utilisation of veterinary medical arts and sciences in the prevention of disease, protecting life, and promoting the wellbeing and efficiency of man." The scope of the subject is therefore wide and of a multidisciplinary nature. The applicant was formally appointed to promote the discipline of veterinary public health at Massey University in 1973. However, he has had a major interest in the topic since becoming involved in insecticide toxicity in the early 1960's. This interest led to the development of animal models for the study of human infectious disease, particularly cariogenic streptococci, and the use of gnotobiotic techniques. [From Preface]
This Doctor of Science comprises a number of published works listed in the List of Publications in the attached file. Due to copyright restriction, they are not included here but can be accessed individually from the publisher.
Keywords: Veterinary public health